Generation of Neuronal Progenitor Cells in Response to Tumors in the Human Brain. (3rd January 2014) - Macas, Jadranka; Ku, Min-Chi; Nern, Christian; Xu, Yuanzhi; Bühler, Helmut; Remke, Marc; Synowitz, Michael; Franz, Kea; Seifert, Volker; Plate, Karl H.; Kettenmann, Helmut; Glass, Rainer; et al.
Abstract: Data from transgenic mouse models show that neuronal progenitor cells (NPCs) migrate toward experimental brain tumors and modulate the course of pathology. However, the pathways whereby NPCs are attracted to CNS neoplasms are not fully understood and it is unexplored if NPCs migrate toward brain tumors (high-grade astrocytomas) in humans. We analyzed the tumor-parenchyma interface of neurosurgical resections for the presence of (NPCs) and distinguished these physiological cells from the tumor mass. We observed that polysialic acid neural cell adhesion molecule-positive NPCs accumulate at the border of high-grade astrocytomas and display a marker profile consistent with immature migratory NPCs. Importantly, these high-grade astrocytoma-associated NPCs did not carry genetic aberrations that are indicative of the tumor. Additionally, we observed NPCs accumulating in CNS metastases. These metastatic tumors are distinguished from neural cells by defined sets of markers. Transplanting murine glioma cells embedded in a cell-impermeable hollow fiber capsule into the brains of nestin-gfp reporter mice showed that diffusible factors are sufficient to induce a neurogenic reaction. In vitro, vascular endothelial growth factor (VEGF) secreted from glioma cells increases the migratory and proliferative behavior of adult human brain-derived neural stem and progenitor cells via stimulation of VEGF receptor-2 (VEGFR-2). In vivo, inhibiting VEGFR-2 signaling with a function-blocking antibody led to a reduction in NPC migration toward tumors. Overall, our data reveal a mechanism by which NPCs are attracted to CNS tumors and suggest that NPCs accumulate in human high-grade astrocytomas. Stem Cells 2014;32:244–257